Assessing crack formation and strain distribution in concrete structures using externally installed fiber optic sensors - Henrik Becks; Matthias Högemann; Josef Hegger; Martin Classen (Case Studies in Construction Materials)
The structural integrity of many European bridges is increasingly compromised by rising traffic loads and gradual deterioration. As a result, numerous bridges are no longer able to meet modern safety standards, necessitating either replacement or extensive maintenance in the coming years. In this context, reliable condition assessment and efficient rehabilitation strategies are essential. Unfortunately, assessment of structural integrity and remaining service life is currently mostly based on elaborate visual inspection, which is time-consuming, subjective, and limited in precision. Fiber optic sensors (FOS) offer a more advanced alternative, enabling quasi-continuous, long-range strain measurements in high resolution.This paper utilizes externally applied FOS on concrete surfaces to measure strain distribution, predict crack initiation, and track crack propagation. Wide-ranging mesoscale tests were conducted on both plain and reinforced concrete (RC) specimens under monotonic, cyclic, and fatigue tensile loading to systematically evaluate the accuracy, robustness, and practical applicability of FOS. Two preselected fiber coating materials – namely polyimide and acrylate – were examined in this study. In addition to a detailed analysis of strain distribution and data point dropout (DPD), crack opening and position were calculated using FOS data and compared with conventional measurement techniques such as digital image correlation (DIC). The results demonstrate that externally applied FOS are able to predict crack initiation based on strain measurements well before visible crack formation, and reliably monitor gradual crack opening even after yielding of the reinforcement, offering valuable insights for long-term structural health monitoring.